2008
DOI: 10.1136/jnnp.2007.128389
|View full text |Cite
|
Sign up to set email alerts
|

Variant Creutzfeldt Jacob disease: the second case in Portugal and in the same geographical region

Abstract: We present the second variant Creutzfeldt-Jacob patient in the same district of northwest Portugal as was previously reported. A 14-year-old previously healthy girl had unexplained pain in the left leg, as well as psychiatric disturbances. This was shortly followed by progressive cognitive impairment, ataxia and generalised choreoatethosis. Neuropsychological assessment revealed severe frontal and medial temporal dysfunction, the posterior cortices being spared. An electroencephalogram was normal. CSF 14.3.3 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…His clinical course (32 months) was the longest of any case published to date with autopsy results, although the range of survival times has been reported as 9–39 months1 and one patient treated with intraventricular pentosan sulfate has been reported as alive after 51 months 2. A second case has subsequently been diagnosed by tonsilar biopsy in Portugal3 but is still living. It is of interest that the two patients lived within 20 km of each other.…”
mentioning
confidence: 97%
“…His clinical course (32 months) was the longest of any case published to date with autopsy results, although the range of survival times has been reported as 9–39 months1 and one patient treated with intraventricular pentosan sulfate has been reported as alive after 51 months 2. A second case has subsequently been diagnosed by tonsilar biopsy in Portugal3 but is still living. It is of interest that the two patients lived within 20 km of each other.…”
mentioning
confidence: 97%
“…Herein, we only report the results from the patients for whom a confirmatory diagnosis was available: 95 neuropathologically confirmed sporadic CJD (sCJD) and 287 patients proved to have an alternative diagnosis (non-CJD), as this was our inclusion criteria. Therefore, all probable and possible cases as well as the two cases of variant CJD [32] and three of Fatal Familiar Insomnia (Santana et al, personal communication) that have been identified in our population, were excluded from this study.…”
Section: Patient Characterizationmentioning
confidence: 99%
“…A 16-year-old girl, diagnosed with vCJD at age 14 years and described in detail elsewhere, 3 had progressive clinical deterioration, leading to a persistent vegetative state. MR imaging at 18 months after onset of the disease showed global brain atrophy and widespread restricted cortical diffusion (Fig 1A).…”
mentioning
confidence: 99%